Osady denne rzeki Skródy i ich rola w obiegu metali w środowisku = Bottom sediments of Skróda river and their role in the metals circulation in the environment - Labus, Małgorzata; Mrowiec, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper some metals content in the bottom sediments of Skróda river was discussed. The contamination of the bottom sediments is influenced by the dump material of the "anthropogenic lake district" in the Łęknica region. The analysis of sequential extraction used in this research allowed to define the share of the individual occurrence forms of the metals, and thereby to estimate the presumptive mobility of the components in the environment and the connected risk.
Keywords: osady denne; odpady; metale; Łuk Mużakowa; bottom sediments; metals; waste material; Muskau Bend